2018
DOI: 10.1007/s10753-018-0734-6
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin Protects against CVB3-Induced Acute Viral Myocarditis through Nrf2 Activation

Abstract: Inflammation and oxidative stress are implicated in the pathogenesis of acute viral myocarditis (AVM). Ulinastantin (UTI), an inhibitor of serine protease widely used in treatment of pancreatitis and various inflammatory disorders, displays cardioprotective properties in experimental animals. Although the specific mechanism through which UTI regulates cardiac function is not well explored, evidence suggests that UTI might activate nuclear factor E2-related factor 2 (Nrf2) signaling. In this study, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…UTI reduces the lipid peroxidation as observed by the reduced TBARS levels [ 64 ]. UTI mediated increase in the anti-oxidants (SOD, GSH, CAT) is possibly via upregulation of nuclear factor E2-related factor 2 (Nrf2) gene [ 21 , 22 , 65 ] and activation of Nrf2/NOS pathway [ 66 ]. Also, UTI administration regulates AMPK/NF-kB pathway, and downregulates (toll like receptor) TLR 4 which are further reported to decreases inflammation [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…UTI reduces the lipid peroxidation as observed by the reduced TBARS levels [ 64 ]. UTI mediated increase in the anti-oxidants (SOD, GSH, CAT) is possibly via upregulation of nuclear factor E2-related factor 2 (Nrf2) gene [ 21 , 22 , 65 ] and activation of Nrf2/NOS pathway [ 66 ]. Also, UTI administration regulates AMPK/NF-kB pathway, and downregulates (toll like receptor) TLR 4 which are further reported to decreases inflammation [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…As ferroptosis can have an effect on cardiovascular diseases, it is closely related to clockophagy; we suggest that there is a relationship between cardiovascular diseases and clockophagy. [35]. Furthermore, Ai et al revealed that Nrf2 pathway is downregulated because of the upregulation of the 12/15-lipoxygenase (12/15-LO), which can be inhibited by baicalein through reducing inflammatory cytokine production and oxidative stress [35,36].…”
Section: Nrf2/ho-1 Signaling Axis In Clockophagymentioning
confidence: 99%
“…[35]. Furthermore, Ai et al revealed that Nrf2 pathway is downregulated because of the upregulation of the 12/15-lipoxygenase (12/15-LO), which can be inhibited by baicalein through reducing inflammatory cytokine production and oxidative stress [35,36]. Conversely, Wang et al have demonstrated that the immune and inflammatory processes can also function as a trigger for the activation of Nrf2 [37].…”
Section: Nrf2/ho-1 Signaling Axis In Clockophagymentioning
confidence: 99%
“…Myocarditis involves many myocardial inflammatory diseases, such as acute myocarditis, chronic myocarditis, and inflammatory cardiomyopathies, and inflammatory diseases with cardiomyopathies [5]. Oxidative stress is also an important risk in the pathogenesis of myocarditis [6]. Inflammatory and oxidative stress can affect the left ventricular internal diameter in end diastole (LVIDd) and left ventricular internal diameter in end systole (LVIDs) [7].…”
Section: Introductionmentioning
confidence: 99%